2009
DOI: 10.1103/physrevd.79.124035
|View full text |Cite
|
Sign up to set email alerts
|

Quantum fate of singularities in a dark-energy dominated universe

Abstract: Classical models for dark energy can exhibit a variety of singularities, many of which occur for scale factors much bigger than the Planck length. We address here the issue whether some of these singularities, the big freeze and the big démarrage, can be avoided in quantum cosmology. We use the framework of quantum geometrodynamics. We restrict our attention to a class of models whose matter content can be described by a generalized Chaplygin gas and be represented by a scalar field with an appropriate potenti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 78 publications
5
81
1
Order By: Relevance
“…In these works, it was concluded that once the Universe enters in a genuinely quantum phase; i.e., where coherence and entanglement effects are important, the Universe would evade a doomsdayà la rip. This applies even to the smoother version of these singular behaviours corresponding to a LSBR [41] (see also [43][44][45][46][47]). …”
Section: Introductionmentioning
confidence: 99%
“…In these works, it was concluded that once the Universe enters in a genuinely quantum phase; i.e., where coherence and entanglement effects are important, the Universe would evade a doomsdayà la rip. This applies even to the smoother version of these singular behaviours corresponding to a LSBR [41] (see also [43][44][45][46][47]). …”
Section: Introductionmentioning
confidence: 99%
“…This was a counterexample to what was believed at the time and it was the first discovery of these types of singularity in cosmology with an explicit construction given in [3]. Sudden singularities were further studied in [4][5][6][7][8][9][10][11][12][13]. The Type IV singularity has some phenomenologically appealing applications and implications in cosmology, as was shown in [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 83%
“…Among them is the big freeze singularity [40][41][42], which takes place at a finite scale factor, in a (flat) FriedmannRobertson-Walker (FRW) universe. For example the future big freeze singularity can appear in a FRW universe with a (phantom) generalized Chaplygin gas (GCG) [40].…”
Section: Classification Of the Possible Evolutional Scenarios In The mentioning
confidence: 99%